Design Education in European Countries: Great Britain and Ukraine - Viktor Danylenko; Lesya Danylenko (Journal of Visual Art and Design, 2021)
In this study, consideration was given to the evolution of design education in the UK and Ukraine. A review was conducted by comparing the following main parameters of the design education sphere in both countries: the historical background of its emergence in the 19th century, the dynamics of the development of higher institutions of design education during the 20th century, as well as quantitative and qualitative indicators of design education at the beginning of the 21st century. In the conclusion two main polar properties of contemporary design education are defined, namely: the ability to prepare for gradual entry into modern practical work/business on the one hand and thorough classical artistic preparation on the other. It has been suggested that with humanity approaching the super-hi-tech era, the tendency of design education in Ukraine, unlike in Britain, towards the second of these properties has a positive potential in preserving human-centric values in contemporary design.